Accountability in waqf mangement: learning from praxis of nongovernmental organisation (NGO) - Osman, Ahmad Zamri (2010)

(untitled)
The paper aims to explore a conceptual framework in which improvement on waqf management may be made focusing on its relationship with beneficiaries. The study uses accountability as the main theoretical lens informing this, where waqf management does not merely see beneficiaries as the passenger in the relationship, rather, as one of the means to improve waqf management. Drawing from NGO accountability literatures, the paper looks at the potential of the holistic accountability where the notion of downward accountability augments the conventional upward accountability. While effort to improve the effectiveness of waqf management tends to focus on upward accountability to board of trustee,there may be a huge potential to listen to and to have dialogue with beneficiaries. An improved accountability relationship downwardly to beneficiaries offers an opportunity for an improvement on the effectiveness and efficiency of waqf management. This is essentially a conceptual paper in which the empirical study is in progress. In presenting the conceptual elements, the paper draws experience from NGO accountability literature and explores the extent to which a theoretical understanding of holistic accountability may offer important insight into the way management of waqf may be improved.